The intermediate effect of earnings per share between influencing factors and financial performance (Entrepreneurship Journal for Finance and Business, 2021)
This study aimed to search the factors affecting earnings per share and financial performance in joint stock companies operating in the Iraq Stock Exchange (industrial sector), where the impact of internal and external factors on earnings per share and on Financial performance, and the impact of earnings per share on financial performance on the other hand, as the problem of the study raised questions about the nature of the impact relationship between the three variables of the study. The researchers adopted a scientific approach using the descriptive analytical approach and using the statistical program (spss v23) to find ratios and frequencies and examine the efficiency of the measurement tool. As well as the program (AMOS V23) in process of analyzing data according to the Structural Equation Modeling (SEM) method to find the values of the regression coefficients, and to analyze the nature of direct and indirect (median) relationships. One side and the earnings per share on the other hand, and that there is a positive impact relationship directly for earnings per share on financial performance, and that there is an indirect positive impact relationship for awareness. The internal and external burden on financial performance through earnings per share, and there is a variation in the impact relationship from one factor to another. The researchers recommended the necessity of directing these factors programmatically to serve the company and try to exploit them optimally to achieve the highest profit